2022
DOI: 10.31958/jt.v25i2.5804
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Mindfulness Counseling to Improve Orphan Adolescents’ Subjective Wellbeing

Abstract: The main problem in this study is the lack of subjective well-being levels of orphan adolescents. The purpose of this study was to reveal empirical data related to the effectiveness of mindfulness counseling to improve the subjective well-being of orphan adolescents. The population of this research is teenagers who live in Panti Sosial Bina Remaja Padang Panjang, West Sumatra. To measure the level of subjective wellbeing using an instrument namely subjective wellbeing scale that has 32 items. The research samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Group counseling can be an effective method in helping students overcome difficulties in making career decisions (Duru, 2022). Research conducted by Silvianetri et al (2022) The results of research conducted by xxx show that mindfulness counseling is effective in improving subjective well-being. In the study, the experimental group given mindfulness counseling showed an increase in subjective well-being of 43.4 points compared to the control group given lectures.…”
Section: Introductionmentioning
confidence: 99%
“…Group counseling can be an effective method in helping students overcome difficulties in making career decisions (Duru, 2022). Research conducted by Silvianetri et al (2022) The results of research conducted by xxx show that mindfulness counseling is effective in improving subjective well-being. In the study, the experimental group given mindfulness counseling showed an increase in subjective well-being of 43.4 points compared to the control group given lectures.…”
Section: Introductionmentioning
confidence: 99%